Karakteristik Tb Paru Dewasa Di Balai Besar Kesehatan Paru Masyarakat Surakarta Tahun 2015 - Wibowo, Anton Tri, Dr. Faizah Betty Rahayuningsih AS.Kep., M.Kes, Arief W. Jadmiko, S.Kep., Ns., M.Kep (2016)
At the present cases of Tuberculosis in Indonesia are still high. A new case Tuberculosis smear positive treatment at BBKPM of Surakarta in 2013 recorded 233 cases and increase in 2014 which 277 cases. in 2015 reduced 260 cases pulmonary Tuberculosis smear positive. High incidence pulmonary Tuberculosis can be caused lack of the application of DOTS strategy with tightly. Factors affecting the incidence of pulmonary Tuberculosis (age, gender, education, source of payment , nutritional status, and knowledge) and extrinsic factors (ventilation, lighting, and residential density). The purpose is to know intrinsic factor which age, sex, education level, work, and source of payment pulmonary Tuberculosis of patients at BBKPM of Surakarta in 2015. The kind of research used is that research is descriptive analytic, with the approach study retrospective. population research was all of Tuberculosis patients pulmonary positive adult in BBKPM of Surakarta in 2015 account 260 patients. The sample are 72 persons with taking sample with systematic random sampling. An instrument used is checklist, the source of data using secondary data. Data analysis the research uses the frequency and the percentage in each lab data. The results of the study is known 66,7 % respondents was between 15 -55 years, 59.7 % respondents male sex, 44,1 % respondents have high school, 48.6 % respondents working as entrepreneurs and 62.5 % respondents use BPJS health in the cost of their treatment pulmonary Tuberculosis.